Brief History and Characterization of Enhanced Respiratory Syncytial Virus Disease - Acosta, Patricio Leandro (2015)
In 1967, infants and toddlers immunized with a formalin-inactivated vaccine against respiratory syncytial virus (RSV) experienced an enhanced form of RSV disease characterized by high fever, bronchopneumonia, and wheezing when they became infected with wild-type virus in the community. Hospitalizations were frequent, and two immunized toddlers died upon infection with wild-type RSV. The enhanced disease was initially characterized as a "peribronchiolar monocytic infiltration with some excess in eosinophils." Decades of research defined enhanced RSV disease (ERD) as the result of immunization with antigens not processed in the cytoplasm, resulting in a nonprotective antibody response and CD4(+) T helper priming in the absence of cytotoxic T lymphocytes. This response to vaccination led to a pathogenic Th2 memory response with eosinophil and immune complex deposition in the lungs after RSV infection. In recent years, the field of RSV experienced significant changes. Numerous vaccine candidates with novel designs and formulations are approaching clinical trials, defying our previous understanding of favorable parameters for ERD. This review provides a succinct analysis of these parameters and explores criteria for assessing the risk of ERD in new vaccine candidates.